Penggunaan Insektisida Rumah Tangga dalam Pengendalian Populasi Aedes aegypti di Daerah Endemis Demam Berdarah Dengue (DBD) di Jakarta Timur - Heni Prasetyowati; Endang Puji Astuti; Andri Ruliansyah (Loka Litbang Kesehatan Pangandaran, 2016)
High incidence of dengue fever in East Jakarta makes the government and the community to do a variety of control measures. The use of household insecticides became the most widely used by the people in efforts to control the population of Aedes spp. The purpose of this study was to determine the description of the use of household insecticides in dengue endemic area in East Jakarta. Data were collected during May 2015 with research sites in the region Puskesmas Matraman, Jatinegara and Duren Sawit. In each of the health center, the area was taken with the highest endemicity last three years. Interviews and observations conducted in 100 houses selected randomly in each area (total 300 houses). Interviews about the household use of insecticides to adult respondents surveyed who lived that house. Interview data were analyzed descriptively to describe the use of insecticides, the type of formulation, the active ingredient types, frequency and time of use. Based on the interview as much as 227 (75.67%) of respondents said using household insecticides over the last three years, while 73 (24.33%) of respondents claimed not to use it. Most people choose to use the type of lotion and aerosol formulations. The active ingredients, which are predominant circulating, are DEET, praletrin, d-aletrin and the d-fenotrin. The frequency of household insecticide use by communities in the study area ranged from <1-14 per week, as well as the use of the majority of the time is used at night.